2015
DOI: 10.1111/vop.12255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of once daily topical 0.3% naltrexone on tear parameters and corneal sensitivity in dogs with uncontrolled keratoconjunctivitis sicca: a double‐masked randomized placebo‐controlled clinical trial

Abstract: Objective To determine the effect of once daily topical 0.3% naltrexone (NTX) on tear production, tear film breakup time (TFBUT), and corneal sensitivity in dogs with uncontrolled keratoconjunctivitis sicca (KCS). Animals studied Sixteen dogs with uncontrolled KCS. Procedures A randomized placebo-controlled trial was performed in 16 dogs with topical 0.3% NTX once daily or topical saline solution drops once daily. A baseline was obtained at week 0 for tear production (Schirmer tear test 1 and 2-STT1, STT2), TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Although values of such parameter decreased in accordance with the disease severity, statistical significance was only observed between the eyes graded as mild and severe. Considering the 32 eyes with KCS, TFBUT values (5.93 seconds, range 2.10 to 11.2 seconds) were similar to those reported in another research (6.2 to 7 seconds) conducted in dogs with KCS (Chen and Powell, 2015). In the study of Chen and Powell (2015), STT values ranged from 0 to 13mm/minute, but authors did not separate the eyes with KCS in different categories.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although values of such parameter decreased in accordance with the disease severity, statistical significance was only observed between the eyes graded as mild and severe. Considering the 32 eyes with KCS, TFBUT values (5.93 seconds, range 2.10 to 11.2 seconds) were similar to those reported in another research (6.2 to 7 seconds) conducted in dogs with KCS (Chen and Powell, 2015). In the study of Chen and Powell (2015), STT values ranged from 0 to 13mm/minute, but authors did not separate the eyes with KCS in different categories.…”
Section: Discussionsupporting
confidence: 80%
“…Considering the 32 eyes with KCS, TFBUT values (5.93 seconds, range 2.10 to 11.2 seconds) were similar to those reported in another research (6.2 to 7 seconds) conducted in dogs with KCS (Chen and Powell, 2015). In the study of Chen and Powell (2015), STT values ranged from 0 to 13mm/minute, but authors did not separate the eyes with KCS in different categories. In diabetic dogs with qualitative KCS, TFBUT was 6.55 seconds, also similar with the ones observed in our study (Cullen et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, TBUT values in Shih Tzu dogs for each stage were similar to those described by Madruga et al (2018) in a study that evaluated dogs of different breeds with mild, moderate, and severe KCS. Moreover, dogs with KCS, regardless of the stage, have TBUT values ranging from 5.93 to 11 s (Oria et al 2013, Chen & Poweel 2015, Dos Santos et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…According to these results, preclinical reports in animals demonstrated that continuous suppressions of receptors with NTX applied topically resulted in reversal of dry eye and re-establishing the corneal sensitivity in diabetic animals without effect in normal ones [ 109 , 110 ]. Additionally, LDN (1–5 mg/daily) has been effective and well-tolerated for alleviating refractory neuropathic pain in diabetic patients [ 108 , 111 ].…”
Section: Discussionmentioning
confidence: 99%